Strategic Planning of Academic Supervision in Fostering a Qur’anic Generation: The Perspective of Integrated Islamic Schools - Murniati AR; Nasir Usman; Suci Nabilah Balqis (Universitas Nurul Jadid, 2025)
Islamic education currently faces major challenges in forming a Qur'anic generation amidst globalization and the growing moral crisis. Integrated Islamic Schools (SIT) offer an educational model that integrates Islamic values ​​with quality formal education. In this context, the role of teachers is very strategic, so their professional development becomes very important. Academic supervision serves as an important instrument in guiding teachers through a collaborative, reflective, and systematic approach. This study aims to analyze the strategic planning of academic supervision in forming a Qur'anic generation at SIT. With a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings of the study indicate that supervision planning includes goal setting, target identification, scheduling, preparation of procedures, and active involvement of teachers through pre-supervision activities. This pre-supervision step helps school leaders understand teacher readiness and design more focused supervision. The supervision process not only includes pedagogical aspects but also emphasizes the integration of Islamic values ​​in teaching. Therefore, the academic supervision planning strategy at SIT has proven effective in improving teacher quality while strengthening students' Qur'anic character, in line with the vision of holistic education that balances spiritual, intellectual, and moral development.